2019
DOI: 10.1111/jgh.14794
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal treatment of dyslipidemia in patients with nonalcoholic fatty liver disease

Abstract: Background and Aim Nonalcoholic fatty liver disease (NAFLD) patients often have dyslipidemia, and optimal treatment of dyslipidemia lowers the risk of cardiovascular disease and mortality. Our aim was to study the prescription of statin and low‐density lipoprotein cholesterol treatment targets in NAFLD patients. Methods Consecutive NAFLD patients attending five clinics in Asia were included in this study. The 10‐year cardiovascular disease risk was calculated based on the Framingham Heart Study, and patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
0
32
1
Order By: Relevance
“…328 Strict control of low density lipoprotein cholesterol (LDL-C) is emphasized because many NAFLD patients treated with statins still did not meet their LDL-C treatment targets, which can itself increase the incidence of CVD. 329 A common adverse effect of statins is the asymptomatic elevation of aminotransferases, which usually appears within one year of starting statins and recovers spontaneously. 330 This increase in liver enzyme levels depends on the statin dose.…”
Section: -2-2 What Is the Effect Of Moderate Or Less Alcohol Consumption?mentioning
confidence: 99%
See 1 more Smart Citation
“…328 Strict control of low density lipoprotein cholesterol (LDL-C) is emphasized because many NAFLD patients treated with statins still did not meet their LDL-C treatment targets, which can itself increase the incidence of CVD. 329 A common adverse effect of statins is the asymptomatic elevation of aminotransferases, which usually appears within one year of starting statins and recovers spontaneously. 330 This increase in liver enzyme levels depends on the statin dose.…”
Section: -2-2 What Is the Effect Of Moderate Or Less Alcohol Consumption?mentioning
confidence: 99%
“…In a study using data from the National Health Information database of South Korea, statin treatment decreased not only the risk of NAFLD occurrence but also the development of fibrosis attributed to NALFD, regardless of diabetes mellitus [ 326 ]. Strict control of low density lipoprotein cholesterol (LDL-C) is emphasized because many NAFLD patients treated with statins still did not meet their LDL-C treatment targets, which can itself increase the incidence of CVD [ 327 ]. A common adverse effect of statins is the asymptomatic elevation of aminotransferases, which usually appears within 1 year of starting statins and recovers spontaneously [ 328 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Although the association between lifestyle habits and NAFLD has been well studied, clinicians and policymakers need to identify areas of deficiency so as to prevent and manage NAFLD. The controlled attenuation parameter (CAP)‐Asia study is a prospective multi‐centre study of real‐world patients with NAFLD in Asian centres and is a good platform to compare the clinical characteristics and management of NAFLD patients in different Asian countries and regions 17 . In the current study, we aimed to compare lifestyle habits of NAFLD patients in different Asian regions and explore the association between lifestyle habits and the severity of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption should be limited to 2-3 drinks per week in women and 4-5 drinks per week in men and avoided in patients with advanced fibrosis (67,68), although high-quality data on the exact risk of progressive liver disease in patients with advanced fibrosis are still needed. Many PCPs and nonhepatologists discontinue statins when liver enzymes are elevated (9,69,70). However, numerous studies have also demonstrated that statins are safe and efficacious in patients with NAFLD and NASH, and they can be used to treat dyslipidemia in these patients, including those with compensated cirrhosis.…”
Section: Managementmentioning
confidence: 99%